Maternal serum advanced glycation end products level as an early marker for predicting preterm labor/PPROM: a prospective preliminary study. (18th August 2019) - Kansu-Celik, Hatice; Tasci, Yasemin; Karakaya, Burcu Kisa; Cinar, Mehmet; Candar, Tuba; Caglar, Gamze Sinem
Abstract: Objective: To evaluate the value of maternal serum advanced glycation end products (AGEs) level at 11–13 weeks' gestation for the prediction of preterm labor and or preterm premature rupture of membranes (PPROM). Materials and methods: This prospective cross-sectional study is performed in a university-affiliated hospital between February and April 2016. The participants of this study are low-risk pregnant women. Blood samples for maternal AGEs level were collected in the first trimester of pregnancy and all women completed their antenatal follow-up and delivered in our center. During the follow-up 21 women developed preterm labor/PPROM. The first trimester maternal AGEs levels of preterm labor/PPROM cases were compared with uncomplicated cases ( n  = 25) matched for age-parity and BMI. The predictive value of AGEs levels for preterm labor/PPROM was also assessed. Results: First-trimester AGEs levels were significantly higher in cases complicated with preterm labor/PPROM (1832 (415–6682) versus 1276 (466–6445) ng/L, p  = .001 and 1722 (804–6682) versus 1343 (466–6445) ng/L, p  = .025). According to receiver-operating characteristic curve analysis, the calculated cut off value of AGEs was 1538 ng/L with the sensitivity 91.7%, specificity 73.8%; and the negative and positive predictive values were 91.6% and 29.5%, respectively. Conclusions: For the prediction of preterm labor/PPROM, the relatively high AGEs levels in the first trimester might be a useful marker.